The Use of Think Pair Share of Cooperative Learning to Improve Weak Students’ Speaking Ability - Kaur Swaran Singh, Charanjit; Ramachandran, Arnita; Singh Masa Singh, Tarsame; Eng Tek, Ong; Md Yunus, Melor; Mulyadi, Dodi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to improve weak ESL learners’ speaking abilities using Think Pair Share (TPS). The study intends to find out the difficulties faced by the learners in speaking, how Think Pair Share of cooperative learning can improve speaking skills, and ESL learners’ perception of the use of TPS in speaking activities. The study employed an action research design. Twenty-four Form 4 ESL learners participated in this study. Data collection included the teacher’s reflective entry and focus group interviews with the ESL learners. The results show that Think Pair Share improves learners speaking abilities and has a huge impact on boosting learners’ confidence levels to speak in English.